Overall Survival in Heart Disease–Related Death in Non-Small Cell Lung Cancer Patients: Nonimmunotherapy Versus Immunotherapy Era: Population-Based Study - Safi, Mohammed; Kanesvaran, Ravindran; Alradhi, Mohammed; Al-Danakh, Abdullah; Ping, Feng; Al-Sabai, Najeeb; Shan, Xiu; Liu, Jiwei (Frontiers in Oncology, 2020)
The cardiotoxicity during immunotherapy administration leads to mortality by more than 42% and heart disease-related mortality among immunotherapy-linked cancers is still considered to be underestimated. In this study, the advanced stage of non-small cell lung cancer (NSCLC) with heart disease-related death was selected in accordance with immunotherapy approval time. NSCLC was searched on the Surveillance, Epidemiology, and End Results (SEER) program. Results showed that 538 advanced NSCLC cases, those dominated by men and elderly people aged more than 70 years had a high percentage of heart disease-related death in both eras. The difference between contemporary groups was fairly non-significant (P = > 0.05). The overall survival (OS) of all-cause mortality difference showed improved survival in the immunotherapy group (P = 0.0001). In the study of heart disease-related death survival with adjusted the data, the NSCLC patients showed significant lower survival in the immunotherapy era compared with non-immunotherapy era (P = 0.003; hazard ratio [HR] = 1.31; 95% CI = 1.099–1.57). In the multivariate analysis of NSCLC-related immunotherapy, histology revealed that the non-squamous cell type had an independent risk for lower OS than the squamous cell type (P = 0.04; HR= 0.74; CI = 0, 55- 0.99). The results demonstrated the survival benefits for NSCLC in immunotherapy; however, in heart disease-related death, immunotherapy in patients with NSCLC showed decreased OS. This study highlighted that NSCLC patients should be highly monitored during immunotherapy administration and further assessment needed.